The quest for Cardenio Shakespeare, Fletcher, Cervantes, and the lost play - Carnegie, David, 1943-; Taylor, Gary, 1953- (Oxford : Oxford University Press, 2012)
Bringing together leading scholars, critics, and theatre practitioners, this collection of essays is devoted to 'The History of Cardenio', a play based on Don Quixote and said to have been written by Shakespeare and the young man who was taking his place, John Fletcher.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Second maiden's tragedy -- Authorship; Shakespeare, William, -- 1564-1616 -- Authorship; Fletcher, John, -- 1579-1625 -- Authorship